The Microstructure in an Al–Ti Alloy Melt: The Wulff Cluster Model from a Partial Structure Factor - Xiaohang Lin (MDPI AG, 2021)
In the present work, the Wulff cluster model—which has been proven to successfully describe pure metals, homogeneous alloys, and eutectic alloys—has been extended to complex binary Al80Ti20 alloys, containing intermetallic compounds. In our model, the most probable structure in metallic melts should have the shape determined by Wulff construction within the crystal structure inside, and the cluster’s size could be measured by pair distribution function. For Al80Ti20 binary alloy, three different types of clusters (Al cluster, Al3Ti cluster, and Ti cluster) were proposed. Their contributions in XRD results are investigated by a comparison with the partial XRD pattern. Ti–Ti and Al–Ti partial structural factors are completely contributed by a pure Ti cluster and an Al3Ti cluster, respectively. Al–Al partial structural factor is contributed not only by a pure Al cluster but is also related to part of the Al3Ti cluster. The simulated XRD curve shows a good agreement with the experimental partial I(θ), including the peak position, width, and relative intensity.